Features of skin regeneration of adult animals after burn injury and the use of chitosan films. - Kornienko, V. V.; Holubnycha, V. M.; Husak, E. V.; Kalinkevich, O. V.; Oleshko, O. M.; Hapchenko, A. V.; Pogorielov, M. V. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. In recent years, protective wound coatings from chitosan have been obtained, which represent a semi-permeable biological membrane.The aim of the study was to examine the morphofunctional features of the skin after burn injury using chitosan films for wound healing. Methods. Using a complex of cytological, planimetric and histomorphometric methods the main features of the burn wounds regeneration were investigated. The burn wounds of IIIb degree were modeled on the 9 months old rats. Animals of the experimental group were treatedwith chitosan films(degree of deacetylation 87 % and molecular weight 700 kDa). The material for the studies was collected on the 1st, 3rd, 7th, 14th and 21st days after injury. Results. The use of chitosan films leads to a decrease in the total area of the burn and the relative area of necrosis in animals of the experimental group. As result of chitosan films application a significant difference of the wound area reduction (in percentage per day) was observed from the 1st to 3rd and from 4th to 7th days. Chitosan membranes cause a decrease in the number of leukocytes and the percentage of neutrophils starting from the 1 day of observation. The percentage of macrophages gained the maximum values on the 7th day. In contrast to the control group in animals of the experiment, the fibroblasts were identified on the 3rd day. The growth of granulation tissue is characterized by an increase in both the relative area and diameter of its vessels in the earlier period– on the 3 days after injury. Conclusion. Creating an optimal wound environment, stimulation migration of neutrophils and activation of their activity with chitosan lead to the intensification of wound cleaning from dead tissue, reduce the inflammationand edema. The use of chitosan films promotes the blood vessels fomation, stimulates theearlygrowthof granulation tissue, improves epithelialization of the woundand regulates formation of the scar tissue.